Checklist of Occurrences of Marine Crabs (decapods, crustaceans) and their Relationship to Environmental Factors in the Coast Al-Fao Port, Iraq - Al-Baghdadi, Nada M.; Al-khafaji, Khaled Kh.; Kadhim, Saba A. (Mesopotamian Journal of Marine Sciences, 2025)
This work aimed to clarify the importance of the seasonal and spatial distribution of crab populations at two stations that were close in location but differed in their impact on environmental factors (pH, salinity, dissolved oxygen in the water, and water temperature). One station was located close to the coastal zone, and the other was located 5 km from the coastal zone, towards the middle of the sea. Study stations represent newly formed environments. A checklist of crabs associated with the coast of the Greater Faw Port presented, which presently comprises 20 crab species within 11 families (Macrophthalmidae, Camptandriidae, Pilumnidae, Portunidae, Matutidae Galenidae, Sesarmidae, Dorippidae, Ocypodidae, Dotillidae, and Grabidae) which were the most diverse and occurrence of families in the Arabian Gulf. Specimens of crab species Metapograpsus messor (Forskål, 1775), Metapograpsus thukuhar (Owen, 1839) and Pilumnopeus serratifrons (Kinahan, 1856) were encountered for the first time on the Iraqi coast. Samples were collected seasonally from January 2023 to February 2024. The crabs were hand-caught during the low tide period during the day among rocks in the coastal area. The study discussed how environmental changes are primarily linked to seasonal cycles, while they are more closely related to the presence and distribution of crabs near or far from the coast. Temperature was found to have the greatest influence on species presence, indicating that species prefer relatively cooler seasons. This may reflect the sensitivity of some species to changes in salinity concentration. The abundance of dissolved oxygen in the water also enhances the presence of some species, compared with previous studies conducted on the coast of the Al-Faw region